Improving broiler growth and immunity with encapsulated Cosmos caudatus and Andrographis paniculata extracts at high stocking density - Agusetyaningsih, I.; Krismiyanto, L.; Yudiarti, T.; Widiastuti, E.; Sari, D. A. P.; Pawesti, S. D.; Sugiharto, S. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
The community's growing demand for chicken meat as an animal protein source has presented farmers with the challenge to alter the care of broiler chickens by using high cage density. The aim of this study is to investigate the effect of diet supplementation with encapsulated extract of kenikir (Cosmos caudatus) and bitter (Andrographis paniculata) extracts on broiler diet to growth perfor-mance, immunity status, and carcass proportion. A total of 370 day-old Cobb broiler chicks, weighing 45.25 ± 0.89 g, were divided into five groups: T0: control, basal diet + density 10 chicks/m2, T1: basal diet + density 16 chicks/m2, T2: basal diet + density 16 chicks/m2 + Cosmos caudatus 1 g/kg feed, T3: basal feed + density 16 chicks/m2 + Andrographis paniculata 1 g/kg feed, T4: basal feed + density 16 chicks/m2 + Cosmos caudatus 0.5 g/kg feed + Andrographis paniculata 0.5 g/kg feed). At the end of the study, the blood sample and internal organ were collected to further analysis. The final weights of groups T2, T3, and T4 were better than T0 and T1, while T1 has the lowest weight among the other groups. Chicks in T0, T2, T3 and T4 had lower PDW levels compared to T1. Chicks in T4 have a high-er jejunum villi height compared to T0, T1, T2 and T3 groups. The treatments did not affect the small intestine and giblets relative organ wights (P>0.05). The group of T0, T2, T3, and T4 have a fewer duo-denum lesion compared to T1. The group of T2, T3, and T4 have a better structure in jejunum cells compared to T0 and T1. Lesion score of Bursa Fabricius and spleen were greater in T3 and T4 com-pared to T0, T1 and T2 groups. And T1 have the lowest ND antibody compared to other groups. In con-clusion, giving encapsulation of kenikir (Cosmos caudatus) and bitter (Andrographis paniculata) ex-tracts on broiler diet can improve production performance and immune status of broiler chickens.